Perencanaan Model Penanggulangan Kemiskinan Petani Berlahan Sempit - Budiman Notoatmojo (The Winners, 2003)
In general, the goal of the study is to develop planning model for alleviation for the poor from small farmers land-holding. Specifically the main objective is to delineate the poorness of small land holding and how to recommend  the alternative direct agro business investment planning model which will be given to them. The analytical methodology used statistical model entropy and coefficient of variation with the main parameter of farmers income and its stability. The sampling taken from 6 kabupaten in 3 provinces, Central and East Jawa and West Sumatra. Mostly the model used is integrated farming system (livestock, food crops, and perennial crops).